The association between brominated flame retardants exposure with Parkinson’s disease in US adults: a cross-sectional study of the National Health and Nutrition Examination Survey 2009–2016 - Lv, Jia-jie; Zhang, Yi-chi; Li, Xin-yu; Zhang, Lin-jie; Yixi, Zhuo-ma; Yang, Cheng-hao; Wang, Xu-hui (Frontiers in Public Health, 2024)
Background: Increasing evidence suggests that environmental factors play a crucial role in the pathogenesis of Parkinson's disease (PD). Humans are simultaneously exposed to multiple brominated flame retardants (BFRs) in the environment. However, the relationship between BFRs and PD remains unclear. This study was designed to investigate the overall association between BFRs and PD in a nationally representative US population and to further identify significant chemicals. Methods: This study used data from 7,161 NHANES participants from 2009 through 2016. The serum BFRs registry included PBDE-28, PBDE-47, PBDE-85, PBDE-99, PBDE-100pbde-100, PBDE-153, PBDE-154, PBDE-183, PBDE-209 and PBB-153PBR-153. A survey-weighted generalized logistic regression model with restricted cubic splines (RCS) was used to evaluate the association between single BFRs exposure and periodontitis. Meanwhile, weighted quantile sum (WQS) regression and Bayesian kernel machine regression (BKMR) were used to evaluate the overall association of mixed frankincense powder with periodontitis and to identify significant chemicals. Sensitivity analysis was performed to evaluate the robustness of the results. Results: Among the 7,161 participants, 65 had Parkinson's disease (PD). PD patients were older (mean age 57.79 vs 46.57 years) and had a higher proportion of females (70.86%) compared to non-PD participants. Serum levels of PBB-153 were significantly higher in those with PD. Logistic regression analyses revealed a non-linear, inverted U-shaped relationship between serum PBB-153 and PD risk. The risk of PD increased with higher PBB-153 levels up to the 3rd quartile (Q3), beyond which the risk declined (Q3 vs Q1: OR=4.98, 95% CI=1.79-13.86; Q4 vs Q1: OR=3.23, 95% CI=1.03-10.08). PBB-153 (43.40%), PBDE-153 (24.75%), and PBDE-85 (19.51%) contributed most to the weighted quantile sum index associated with PD risk. Bayesian kernel machine regression confirmed the inverted U-shaped dose-response pattern for PBB-153 and the overall BFR mixture. Restricted cubic spline analyses corroborated the non-linear relationship between PBB-153 and PD, which was more pronounced among women and those aged 37-58 years. Sensitivity analyses substantiated these findings. Conclusion: This nationally representative cross-sectional study revealed a novel non-linear, inverted U-shaped relationship between serum levels of the brominated flame retardant PBB-153 and Parkinson's disease risk in U.S. adults.